Correlation between artificial and natural weathering of hemp fibers reinforced polypropylene biocomposites. (February 2018) - Badji, Célia; Beigbeder, Joana; Garay, Hélène; Bergeret, Anne; Bénézet, Jean-Charles; Desauziers, Valérie
Abstract: The degradation behaviors of hemp fibers reinforced PP biocomposites under outdoor and artificial weathering were compared to establish a correlation. For this purpose, several measurements were performed throughout the expositions. Mechanical performance was tested by three-point bending test. Microstructure and chemical composition changes were also assessed. Otherwise, visual aspect and topography were determined. The artificial weathering effectively accelerated the degradation mechanisms. Oxidation pathways and surface aspect alteration of both polymer and biocomposites occurred faster. However, whereas biocomposites were mainly subjected to outdoor conditions due to high sensitivity of hemp fibers, neat PP was globally mostly affected by laboratory chamber conditions. Its oxidation rate largely outstripped reinforced materials ones. Principal Component Analysis was used for verifying the differences of variables correlations profiles between artificial and exterior ageing dataset in order to compare the degradation mechanisms. Through the statistical analysis, some attempts were made to find equivalence between artificial and outdoor weathering times thanks to properties degradation rate similarities. Highlights: Artificial ageing accelerated degradation phenomenon having occurred outside. Degradation mechanisms are compared thanks to statistical Principal Component Analysis. Temporal equivalence between weathering is proposed through statistical way.